Case Report: Human Dermatitis Linked to Ornithonyssus bursa (Dermanyssoidea: Macronyssidae) Infestation in Portugal - Waap, Helga; Aguin-Pombo, Dora; Maia, Maria (Frontiers in Veterinary Science, 2020)
Ornithonyssus bursa (Berlese, 1888), also known as the tropical fowl mite, is a blood-feeding ectoparasite of domestic and wild birds. It is considered a serious pest to poultry in warm and tropical climates and has been reported to attack humans, causing gamasoidosis. Avian-mite dermatitis may be difficult to recognize and misdiagnosed as bites from other arthropods. The present report describes two cases of human dermatitis linked to O. bursa infestation. Both cases occurred in an apartment in a residential area in Oeiras, Portugal, where two members of the same family presented with pruritic erythematous skin eruptions disseminated over their body over a period of four months. The lesions were located mostly in the pelvic, gluteal, coccygeal, and perineal regions, and also on the neck, wrists and torso. On inspecting the mattresses and the covers of the bedrooms, three mites approximately 1mm long by 0.5 mm wide were found. The three specimens were identified as O. bursa. Investigations tracing back the source of infestation, revealed that the mites were carried over from chickens raised 45 km away (Sesimbra, Setúbal) that, after being slaughtered for consumption, had been transported by car to the apartment in Oeiras. The chickens were farmed in an open backyard henhouse that allowed free access to several species of wild birds, including pigeons (Columba livia), turtle doves (Streptopelia decaocto) and sparrows (Passer domesticus). Recent reports suggest that O. bursa may be established in Mediterranean countries, increasing the risk of gamasoidosis. This is the first record linking O. bursa infestation of chickens with human dermatitis in continental Portugal. More research is needed to assess the extent of poultry infestation and evaluate the possible implications for the poultry industry, as well as for human health in Portugal.